An Experimental Study of Conduction Heat Transfer Using Phase Change Material Ice Bag Gel in Bricks - Govari, Muhammad Khoirul; Iwan, Muhammad; Irawan, Doddy; Gunarto Gunarto; Fuazen Fuazen; Fahrezi, Dian; Fahrurrozi Fahrurrozi (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
This experiment investigates the heat transfer characteristics of an ice bag gel phase change material (PCM) incorporated within bricks. The study seeks to investigate the performance of ice bag gel as PCM in improving thermal behavior of building material. The experiment consisted of subjecting brick samples with and without ice bag gel PCM to thermal cycles in a semi-automated laboratory setup. The results indicate that ice bag gel PCM incorporated in bricks exhibited minimal changes and better heat transfer as compared to the dry bricks. It was observed that the ice bag gel PCM registered lower peak temperature and slower rates of temperature drop which means their heat storage and release characteristics were efficient. Furthermore, the ice bag gel system produced a steady radiation flux, indicating that it was able to minimize the effects of temperature variations. These results imply that ice bag gel PCM has the potential to be a green and economical option for enhancing thermal comfort and decrease energy consumption in buildings.